The Role of Islamic Values-Based Entrepreneurship Education and Government Support in Improving Students' Business Success in Islamic Boarding School - Raya Sulistyowati; Farij Ibadil Maula; Angga Martha Mahendra; A'rasy Fahrullah; Wening Patmi Rahayu; Md Fauzi Ahmad (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study analyzes the influence of entrepreneurship education on the success of businesses in Islamic boarding schools, with Islamic values as a mediating variable and government support as a moderating variable. Method: Employing a quantitative approach, the research utilizes a sample of 275 students engaged in business within their Islamic boarding schools. Data analysis uses the Structural Equation Modeling (SEM)-PLS method. Results: The findings indicate that entrepreneurship education significantly positively affects the success of student-led businesses, directly and indirectly, through Islamic values. Furthermore, government support enhances the relationship between entrepreneurship education and business success. Novelty: This research is novel in its integrative approach, combining entrepreneurship education, Islamic values, and government support to understand the factors contributing to business success in Islamic boarding schools. The study emphasizes the importance of collaboration among educational institutions, government, and the Islamic boarding school community in fostering an entrepreneurial ecosystem rooted in religious values, essential for advancing the Sustainable Development Goals (SDGs), particularly in quality education, decent work, and economic growth.